Effects of Low Dose Chronic Radiation and Heavy Metals on Plants and Their Fungal and Virus Infections - A Dmitriev; O Shevchenko; V Polischuk; N Guscha (Data Science Journal, 2009)
The effects of low dose chronic radiation on plant disease resistance and fungal and virus infections have been studied. The results obtained in the 10-km Chernobyl zone demonstrated a decrease in plant disease resistance and appearance of a "new" population of stem rust agents of cereal with a high frequency of more virulent clones. Radionuclide contamination and heavy metals lead to wider virus spread and a higher diversity of virus species. The Chernobyl zone is a territory of enhanced risk and potential threats for the environment. A special type of monitoring of microevolution processes in plant pathogens should provide better understanding of how serious these potential threats are.